Nonlinear finite element study on the improvement of torsional strengthening of RC beams with diagonal shear reinforcement - Subasi, Rojda Orman; Caglar, Naci; Demirtas, Gamze; Ozturk, Hakan (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2024)
Experimental and numerical studies are carried out by many researchers in order to examine the nonlinear behavior of reinforced concrete (RC) beams under the torsion moment and to improve the torsional moment capacity. In this study, a numerical study is performed to investigate efficiency of diagonal shear reinforcement (DSR) on the response of RC beams subjected to pure torsion. A nonlinear numerical model was constituted to simulate the response of the RC beams by using ABAQUS software program and verified with the selected experimental results from literature. The numerical analysis results proved that the nonlinear numerical model is quite successful in simulating the nonlinear behavior of RC beams and DSR makes a very significant contribution to the torsional moment capacity of the RC beam subjected to pure torsion.
Keywords: Nonlinear numerical model; RC beam; pure torsion; diagonal shear reinforcement